Histological Comparison between Biphasic Calcium Phosphate and Deproteinized Bovine Bone on Critical-Size Bone Defects - Brito,Marina Araujo (2021)
Abstract The limited options for bone repair have led to an extensive research of the field and the development of alloplastic and xenogeneic grafts. The purpose of this study was to evaluate bone repair with two bone substitutes: deproteinized bovine bone (DBB) and biphasic calcium phosphate ceramic (BCP) in critical-size defect. A total of 8-mm defects were made in the parietal bones of rabbits (n=12). The animals were divided into three experimental groups: sham (defect filled with a blood clot), DBB (defect filled with DBB), and BCP (defect filled with BCP). After the experimental periods of 15 and 45 days, the animals were euthanized and submitted to histomorphometric analysis. The total defect area, mineralized tissue area, biomaterial area, and soft tissue area were evaluated. A greater amount of immature bone tissue and biomaterial particles were observed in the BCP group compared to DBB and sham at 45 days (p<0.05). There was no difference in the qualitative pattern of bone deposition between DBB and BCP. However, the sham group did not show osteoid islands along with the defect, presenting a greater amount of collagen fibers as well in relation to the DBB and BCP groups. There was a greater number of inflammatory cells in the DBB at 45 days compared to BCP and sham groups. In conclusion, BCP and DBB are options for optimizing the use of bone grafts for maxillofacial rehabilitation. Bone defects treated with BCP showed greater deposition of bone tissue at 45 days.